SISTEM CHARGING 110 VDC SEBAGAI SUPPLY CONTROL CIRCUIT VOLTAGE KUBIKEL 20 KV - Dimas Nur Prakoso; Yuli Prasetyo; Basuki Winarno; Budi Triyono; Santi Triwijaya (ELECTRON Jurnal Ilmiah Teknik Elektro, 2025)
The 110VDC supply at the substation serves as a supply for the control and protection system at the cubicle panel. In addition, the 110VDC battery used as a backup supply plays an important role when the main supply source is lost. Loss of supply 110VDC is fatal to the electrical system. Causes electrical interference cannot be monitored and protection failure. 110VDC batteries may experience voltage drops. There are several ways to keep the battery in good condition when used, one of them with a charging system which functions to maintain the condition battery. This system uses a Buck converter circuit with charging pulses through the duty cycle can distribute high electric current to battery. With a Buck converter output voltage of 111 Volt 6.54 A at duty cycle 55% using dummy load. Test results with a voltage of 110VDC and a current of 5A in testing with dummy load of 10Ω480W obtained voltage output of 103VDC and current of 8.40A, in testing with dummy load of 10Ω400W received voltage output of 136VDC and current of 6.28A, in testing with dummy load of 12Ω500W received voltage output of 122VDC and current of 6.00 A, in testing with dummy load of 15Ω500W received voltage output of 127VDC and current of 5.88 A, in testing with dummy load of 11Ω500W received voltage output of 111VDC and current of 6.54A. From the overall test data by providing a load in the form of a dummy load, an average error of 9.86% was obtained.